Effect of nozzle angle on jet impingement cooling system - Khaider, Abu Bakar (2009)
Cooling system using jet impingement is already widely used in industries nowadays. There were various approaches that have been investigated in order to produce more efficient jet impingement cooling system. This thesis is study about the effect of the nozzle angle on jet impingement in order to identify the relationship in heat transfer. Besides, investigation on spacing distance between nozzle’s edge to the impingement surface and Reynolds number at certain angle also identified in this study. Those studies are needed parallel to the current researchers endeavor for future development of cooling system in global industries. The experiment were perform by vary 3 major parameters such as angle of the nozzle (30⁰, 45⁰, 60⁰, and 90⁰), distance between nozzle’s edge to the impinge surface (H/d= 2, 4, 6, and 8) and also Reynolds number (Re= 2300, 1960,930 and 500).The heat source are heated at 100 ⁰C and cooled down by the flow of air from the nozzle. The heat source temperature after cooling are measured and collected. The result discovers about the relationship nozzle angle for jet impingement cooling system which is heat transfer are more efficient when the angle of nozzle approaching to the normal line as the Nusselt Number are more higher at 90⁰ in range 31.5 w/m2K of heat transfer coefficient compare to the lower angles of the nozzle. Furthermore, higher Reynolds number and close range of distance between nozzle’s edges to impingement surface will also gives high Nusselt number which means both also effective cooling effects for the systems.